تقييم فرص تطبيق إعادة هندسة العمليات الإدارية كمدخل لتبسيط الإجراءات الإدارية دراسة تطبيقية على فرع المصرف العقاري في طرطوس (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يتناول البحث دراسة تقويم فرص تطبيق إعادة هندسة العمليات الإدارية كمدخل لتبسيط الإجراءات الإدارية في فرع المصرف العقاري في محافظة طرطوس،حيث يحاول البحث أن يبين أهمية الهندرة كأحد المواضيع الإدارية الحديثة التي يجب أن تلقى الدعم والتأييد من قبل الإدارة، وتوصيف العمليات الإدارية الحالية والإجراءات المتبعة والعمل على وضع تصور مقترح للعمليات الإدارية بعد تطبيق الهندرة وصولاً إلى خطوات عمل منظمة تساعد في تبسيط الإجراءات الإدرية،وتم استخدام المعاينة القصديّة حيث تمّ توزيع 50 استبانة على العاملين في المصرف،وخلصت الدراسة إلى وجود تأييد ودعم من قبل الإدارة لإمكانية تطبيق مدخل إعادة الهندسة وأن تبسيط الإجراءات بعد تطبيق الهندرة تنعكس إيجاباً على أداء الموظفين ورضا العملاء .This research deals with a study evaluating opportunities to apply the Business Process Reengineering as an input to simplify administrative procedures at the Land Bank branch in Tartous, where research attempts to show the importance of Reengineering as one of modern management topics that must be supported and support by the management, and characterization of the current administrative processes and procedures and work to visualize a proposed administrative processes after application Reengineering up to the steps's work helps to simplify AlajraratAladrah, was the preview intentional use were questionnaire distributed to the employees in the bank, and the study concluded that there was support and support by the management of the possibility of applying the re-engineering entrance and simplify After application procedures Reengineering positively reflected on the staff performance and customer satisfaction.